Information Exchange Pairs Simulation Method Based on Discrete Event Simulation for Autonomous Transportation System - Ji Zhang; Zhenwu Chen; Liang Yang; Zihan Guo; Xianglong Feng; Xiang Liu; Zhijun Huang; Puyang Deng; Xiaochun Zhang; Chen Liang (Journal of Advanced Transportation)
Research on the complicated and indeterminate autonomous transportation system (ATS) has drawn increased interest in order to better address issues associated with contemporary transportation development. Hoping to make transportation more sustainable, economical, safe, convenient, and efficient, researchers try to address the expanding demands with the help of ATS characteristics, i.e., sensing, learning, deciding, and reacting autonomously. The majority of research is focused on the ATS architecture, which is currently in the design phase. To refine the relationship between entities in the architecture, this paper proposes DESIEP, a method based on discrete event simulation (DES) for information exchange pairs (IEPs) in ATS. This method can provide an intelligible description of the information stream while conveniently illustrating the control relationship of sequential logic amongst the entities in the architecture. It helps researchers better understand the running mechanisms driven by internal demands and external technologies of the system so as to diagnose, evaluate, verify, and optimize the designed architecture. Meanwhile, this method also supports further research on the system evolution and architecture analysis, including the functions, logic, and physical architectures of each generation, as well as their mapping relationships and parallel evolution mechanisms.